2022
DOI: 10.15359/ru.36-1.5
|View full text |Cite
|
Sign up to set email alerts
|

Criterios que guían la práctica del profesor de matemáticas en cursos de ciencias básicas para ingeniería

Abstract: El presente estudio tiene como objetivo inferir los criterios que orientan la práctica del profesor universitario para explicar matemáticas en un curso de ciencias básicas en carreras de ingeniería y, en concreto, para explicar derivadas. Se trata de una investigación cualitativa de estudio de caso múltiple que busca comprender la enseñanza del cálculo diferencial a través del análisis de las prácticas de un grupo de siete docentes, y de la reflexión sobre dichas prácticas, cuando implementan sus clases en fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Additionally, engagement with mathematics promotes critical reasoning, decision-making, metacognition, among many other skills (Saha et al, 2020), all of which are imperative for success in today's rapidly changing world (Said et al, 2023). Particularly, two of the most important are procedural and problem-solving skills, and although efforts to enhance the teaching of mathematics are ongoing worldwide, including in Peru, where the existing mathematics education model in schools and universities is being examined for potential transformation and improvement (Garcés-Córdova & Font-Moll, 2022;Garcés Córdova et al, 2021;Maraví Zavaleta, 2021), recent studies revealed that the development of mathematical skills still requires a long process of improvement (Faulkner et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, engagement with mathematics promotes critical reasoning, decision-making, metacognition, among many other skills (Saha et al, 2020), all of which are imperative for success in today's rapidly changing world (Said et al, 2023). Particularly, two of the most important are procedural and problem-solving skills, and although efforts to enhance the teaching of mathematics are ongoing worldwide, including in Peru, where the existing mathematics education model in schools and universities is being examined for potential transformation and improvement (Garcés-Córdova & Font-Moll, 2022;Garcés Córdova et al, 2021;Maraví Zavaleta, 2021), recent studies revealed that the development of mathematical skills still requires a long process of improvement (Faulkner et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In many Peruvian schools, this has led to the overemphasis on algebraic and arithmetic aspects in mathematics subjects, resulting in students acquiring shallow knowledge without a deep understanding, thus encouraging students to seek mechanistic solutions without fostering creativity (Khalid et al, 2020) and leading them to prioritize procedural skills at the expense of important aspects like contextualization (Garcés-Córdova & Font-Moll, 2022;Garcés Córdova et al, 2021). Consequently, students pass through a learning process of mathematical concepts without gaining a profound understanding or a sense of practical application, ultimately resulting in a deficiency in problem-solving skills.…”
Section: Introductionmentioning
confidence: 99%